2020
DOI: 10.1002/cite.202000136
|View full text |Cite
|
Sign up to set email alerts
|

Solid Particle Effects in Centi‐scale Slurry Bubble Columns

Abstract: Both solid particles and column diameter affect the gas holdup and flow regimes in slurry bubble columns, but investigations of the combined effects are not to be found. This study shows the simultaneous impacts on the overall gas holdup and flow regime transitions and determines the dominant effects in slurry bubble columns on the centi‐scale containing solid particle concentrations up to 20 vol %. Additional tomography measurements are presented to visualize the gas phase flow and the spatial gas phase distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
3
0
1
Order By: Relevance
“…In this regard, Li et al [35] also reported that increasing the particle concentration and density result in decreasing the value of gas superficial velocity of the transitions points all. Decreasing the value of superficial gas velocity with increasing the solid concentration was also reported by a plethora of investigators like Mu ¨hlbauer et al [20], Hooshyar et al [44], Abdulrahman [30], Li et al [38], and Mota et al [42]. In this regard, Li et al [38], using the differential pressure fluctuation analysis by Hilbert-Huang transform, reported the gas velocity at the first transition point (homogenous to transition) in the range of 0.058-0.069 m s -1 and the gas velocity at the second transition point is in the range of 0.156-0.178 m s -1 .…”
Section: Flow Regimesupporting
confidence: 68%
See 2 more Smart Citations
“…In this regard, Li et al [35] also reported that increasing the particle concentration and density result in decreasing the value of gas superficial velocity of the transitions points all. Decreasing the value of superficial gas velocity with increasing the solid concentration was also reported by a plethora of investigators like Mu ¨hlbauer et al [20], Hooshyar et al [44], Abdulrahman [30], Li et al [38], and Mota et al [42]. In this regard, Li et al [38], using the differential pressure fluctuation analysis by Hilbert-Huang transform, reported the gas velocity at the first transition point (homogenous to transition) in the range of 0.058-0.069 m s -1 and the gas velocity at the second transition point is in the range of 0.156-0.178 m s -1 .…”
Section: Flow Regimesupporting
confidence: 68%
“…Concerning the effects of gas superficial velocity, it has been reported by Tyagi et al [28], Moshtari et al [47], Mu ¨hlbauer et al [20], Li et al [49], Sines et al [26], Sun et al [45], and Sehabiague [36] that gas hold-up increases with increasing the gas superficial velocity in SBCRs. Other Parameters like the sparger type can also affect the gas hold-up because the sparger type can affect the initial bubble size distribution.…”
Section: Flow Regimementioning
confidence: 93%
See 1 more Smart Citation
“…To determine the gas holdup, either the method of Mühlbauer et al 28 was used or the gasified height was repeatedly read from a scale attached to the outside of the column. In both cases, the relative measurement error is estimated to be less than 1% based on the standard deviation (SD).…”
Section: Methodsmentioning
confidence: 99%
“…, der Extraktion[5][6][7][8][9][10] sowie der Messtechnik[11][12][13] hinzu. Im Bereich der Blasensäulen erfolgt eine kontinuierliche Weiterentwicklung der Errungenschaften in Bezug auf die Suspensionsblasensäulen[14][15][16][17][18], u. a. im Rahmen des BMWi-Projekts ,,Innovative Syntheseprozesse zur Erzeugung chemischer Energieträger aus grünem Wasserstoff in lastflexiblen Blasensäulenreaktoren'' mit der DVGW Forschungstelle am Engler-Bunte-Institut als Projektkoordinator. Damit trägt die aktuelle Forschung direkt zum gesteckten Ziel der Reduzierung der Kohlenstoffkonzentration in der Atmosphäre bei.…”
unclassified